Research on deposition effect of droplets based on plant protection unmanned aerial vehicle: A review - HE Yong; WU Jianjian; FANG Hui; ZHENG Qishuai; XIAO Shupei; CEN Haiyan (浙江大学学报. 农业与生命科学版)
In the process of agricultural sustainable development, diseases and insect pests have always been the focus of attention. Due to the flexibility and convenience, unmanned aerial vehicle (UAV) spray has attracted wide attention in the field of plant protection, and new progress has been made in prevention and control of diseases and insect pests. However, there are still some problems in the UAV spray technology, such as droplet drift and pesticide waste. The deposition effect of droplets is the greatest concern in the UAV spray operation. This paper summarized the characteristics of droplet deposition distribution and the influence factors on droplet deposition and its distribution. Besides, new methods of detecting droplet deposition were listed. The research showed that the deposition effect was influenced by many factors such as flight parameters, natural factors and spray equipment and modes, which should be integrated together in the UAV application, and the wind field below the UAV should be especially included. Moreover, it is quite necessary to develop new types of nozzles and droplet deposition detection technology to provide a guarantee for improving the deposition effect of droplet.